Frontispiece: Clicking the Arsenic–Carbon Triple Bond: An Entry into a New Class of Arsenic Heterocycles. Issue 39 (19th September 2016) - Pfeifer, Gregor; Papke, Martin; Frost, Daniel; Sklorz, Julian A. W.; Habicht, Marija; Müller, Christian
Abstract : Arsenic Heterocycles In their Communication onpage 11760 ff. C. Müller et al. report a hitherto unknown triazaarsole. The synthesis was accomplished through a [3+2] cycloaddition reaction between an arsaalkyne and an organic azide.